Cavernous Hemangioma of the Female Urethra: A Rare Case Report - Ongun, Sakir; Çelik, Serdar; Aslan, Guven; Yorukoglu, Kutsal; Esen, Adil (Urology Journal, 2014)
Genitourinary hemangiomas are rare entities that can affect any portion of the urinary system. The urethra is rarely involved, and most reported cases have occurred in the male urethra. To our knowledge few cases of hemangioma occurring in the female urethra have been reported. We report a cavernous hemangioma of the urethra in a female patient.